Effect of mentoring program on mentees’ academic performance from an Islamic perspective - Azman Ismail,; Kho, Michael Khian Jui; Fariza Md Sham,; Faqih Faqih,; Nor ‘Ain Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2015)
This study examines the relationship between mentoring program and mentees’ academic performance using the survey questionnaires gathered from bachelor degree students in Malaysian higher institutions in Sarawak, Borneo Island. The SmartPLS version 2.0 was employed to test research hypotheses. Outcomes of this test showed two important findings: firstly, communication significantly and positively correlated with academic performance. Secondly, support correlated positively and significantly with academic performance. In sum, this result confirms that mentoring program does act as an important predictor of mentees’ academic performance in the organizations, where this research was conducted.